Adaptive Learning Systems: Bridging Instructional Technology and Personalized Pedagogy through Design Thinking - Nwachukwu, Emmanuel Lucas; Nwamaka Goodness Egbue; Ijeoma VICTOR-NWAKAKU (RADINKA JAYA UTAMA PUBLISHER, 2025)
This review explores how adaptive learning systems, when guided by the principles of design thinking, can bridge the gap between instructional technology and personalized pedagogy. While technology continues to transform education, its impact remains limited when introduced without focus on learner-centered teaching practices. This study argues that technology alone cannot drive meaningful change in the classroom unless it is thoughtfully integrated into the learning process through pedagogical strategies informed by the needs of learners and teachers. The review examines major instructional challenges in contemporary classrooms, including large class sizes, learner diversity, insufficient digital literacy, and inadequate feedback mechanisms. It discusses how design thinking through its stages of empathizing with learners, defining their needs, generating ideas, prototyping solutions, and testing them in the classroom offers a structured yet flexible approach to addressing these challenges. Within this framework, adaptive learning systems emerge as powerful tools for personalizing instruction, delivering differentiated learning pathways, providing real-time feedback, and supporting data-driven decision-making. The review proposes a step-by-step pathway to harmonize technology with pedagogy, emphasizing the importance of empowering educators with analytics and tools, tailoring instruction to individual learners, and creating inclusive environments where learners progress at their own pace. The findings reveal significant implications for practice and policy. It concludes that the fusion of design thinking and adaptive learning has the potential to transform technology from a detached tool into an integral part of teaching and learning, creating more equitable, learner-centered environments that reflect the realities of diverse classrooms and the demands of digital education.